Nutritional habits of the inhabitants of the island of Vis - Missoni, Saša (Array, 2009)
Abstract: The island of Vis belongs to middle Dalmatian group of islands with caracteristics Mediterranean climate. The assumption was that the dominant diet of the inhabitants is also Mediterranean. Such diet is considered to be one of the best for the prevention of many complex and chronic diseases, as confirmed by numerous studies in different parts of the World. This study showed a shift in dietary habits in the direction of a more globalized diet. Such sudden shift may prove to be an important trigger for the development of complex diseases such as diabetes melitus type 2, cardiovascular diseases, gout, as well as certain types of cancer